2012
DOI: 10.18774/448x.2012.9.73
|View full text |Cite
|
Sign up to set email alerts
|

Autoconcepto e identificación social urbana en la ciudad de Copiapó, Chile

Abstract: El siguiente artículo de carácter empírico presenta los principales resultados de una investigación realizada en laciudad de Copiapó, Chile, en la cual se indagaron los autoconceptos y los procesos de identificación social quesus habitantes poseen hacia la ciudad. Respecto a los autoconceptos se realizó un análisis factorial que arrojó oncefactores, los cuales fueron comparados por origen, sexo, edad, nivel educativo, nivel de ingresos familiares y estadocivil de los encuestados, encontrándose diferencias que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Given the evolution that has been evident, for instance, through the development of new projects that have responded in line with urban growth based on the reproduction of capital and financial liquidity, it is relevant to study variables that seek to describe the quality of life of people in cities such as these (Rehner & Rodríguez, 2018). In this context, a previous study observed that various self-concepts regarding the city's inhabitants made it possible to predict the perception of quality of urban life, finding no link between urban social identification and the perception of quality of life in Copiapó (Jorquera, 2012). In this sense, the construct and the proposed instrument enable progress in understanding the individualcity relationship from dimensions that point to personal development and growth in coexistence with the urban environment, which is increasingly dynamic and changing.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the evolution that has been evident, for instance, through the development of new projects that have responded in line with urban growth based on the reproduction of capital and financial liquidity, it is relevant to study variables that seek to describe the quality of life of people in cities such as these (Rehner & Rodríguez, 2018). In this context, a previous study observed that various self-concepts regarding the city's inhabitants made it possible to predict the perception of quality of urban life, finding no link between urban social identification and the perception of quality of life in Copiapó (Jorquera, 2012). In this sense, the construct and the proposed instrument enable progress in understanding the individualcity relationship from dimensions that point to personal development and growth in coexistence with the urban environment, which is increasingly dynamic and changing.…”
Section: Instrumentsmentioning
confidence: 99%
“…Se hace relevante el estudio de variables que apuntan a describir la calidad de vida de las personas en ciudades como esta, dada la evolución que han ido manifestando, por ejemplo, a través del desarrollo de nuevos proyectos que han respondido a una lógica de crecimiento urbano en base a la reproducción del capital y a la liquidez financiera (Rehner & Rodríguez, 2018). En este contexto, en estudio previo se observó que diversos autoconceptos respecto a los habitantes de la ciudad permitían predecir la percepción de calidad de vida urbana, no encontrándose relación entre identificación social urbana y percepción de calidad de vida en la ciudad de Copiapó (Jorquera, 2012). En ese sentido, el constructo y el instrumento propuesto permiten avanzar en el entendimiento de la relación individuo-ciudad desde dimensiones que apuntan al desarrollo y crecimiento personal en convivencia con el entorno urbano, el cual cada vez es más dinámico y cambiante.…”
Section: Instrumentosunclassified